Policing the overdose crisis - Bucerius, Sandra M. (Kriminologisches Journal, 2023)
The opioid overdose crisis in Canada continues to claim the lives of people who use drugs (PWUD). Historically, Canadian crime policy has prioritized crime control forms of surveillance, interdiction and punishment in response to drug use. More recently, harm reduction measures have gained traction, including safe consumption sites (SCS) and police officer use of Naloxone to assist PWUD who have overdosed on opioids. The effectiveness of harm reduction efforts, however, is to some degree contingent on their embrace or acceptance by police agencies and officers. This paper is based on research conducted on the two largest city-level police services in Alberta, Canada. We conducted 94 interviews with officers and had 1,406 officers complete a quantitative survey on issues relating to illicit drugs, overdoses, and fentanyl. Our findings show that police officers generally see opioid use as a serious problem and are concerned about the dangers they face when dealing with PWUD. There is also considerable confusion about the nature and severity of these dangers. Even so, attitudes appear to be shifting and some police officers are changing their practices. In general, our research documents a softening of police attitudes in Canada towards SCS facilities and harm reduction more generally. This greater embrace of a public health orientation could improve the lives of PWUD and their interaction with law-enforcement in Canada. Given the prospect that fentanyl and related synthetic opioids will continue their global spread, these findings should be of interest to an international audience of scholars, police, and healthcare officials.